Oxytocin/vasopressin-like peptide inotocin regulates cuticular hydrocarbon synthesis and water balancing in ants - Koto, Akiko; Motoyama, Naoto; Tahara, Hiroki; McGregor, Sean; Moriyama, Minoru; Okabe, Takayoshi; Miura, Masayuki; Keller, Laurent (Proceedings of the National Academy of Sciences - PNAS, 2019)
Oxytocin/vasopressin-like peptides are important regulators of physiology and social behavior in vertebrates. However, the function of inotocin, the homologous peptide in arthropods, remains largely unknown. Here, we show that the level of expression of inotocin and inotocin receptor are correlated with task allocation in the ant Camponotus fellah. Both genes are up-regulated when workers age and switch tasks from nursing to foraging. in situ hybridization revealed that inotocin receptor is specifically expressed in oenocytes, which are specialized cells synthesizing cuticular hydrocarbons which function as desiccation barriers in insects and for social recognition in ants. dsRNA injection targeting inotocin receptor, together with pharmacological treatments using three identified antagonists blocking inotocin signaling, revealed that inotocin signaling regulates the expression of cytochrome P450 4G1 (CYP4G1) and the synthesis of cuticular hydrocarbons, which play an important role in desiccation resistance once workers initiate foraging.